1999
DOI: 10.3189/172756499781821869
|View full text |Cite
|
Sign up to set email alerts
|

The glacial impact on an exhumed sub-Mesozoic etch surface in southwestern Sweden

Abstract: Along the northern part of the western coast of Sweden, the landscape is characterized by joint-aligned valleys with intervening rock hills. Precambrian bedrock is exposed over large areas and the Quaternary cover is mainly restricted to the bottom of narrow valleys. The well-exposed bedrock exhibits many glacial forms, but recently the major landforms have been interpreted as exhumed sub-Mesozoic etch forms. To gain insight into the relative roles of different processes in shaping the present forms, we studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 16 publications
3
34
0
Order By: Relevance
“…This comparison is consistent with previous work on glaciated granite-gneiss terrains Scandinavia and Greenland (e.g. Bonow, 2005;Lidmar-Bergström, 1989Lindström, 1988;Olvmo et al 1999). …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This comparison is consistent with previous work on glaciated granite-gneiss terrains Scandinavia and Greenland (e.g. Bonow, 2005;Lidmar-Bergström, 1989Lindström, 1988;Olvmo et al 1999). …”
Section: Discussionsupporting
confidence: 82%
“…In contrast, the geomorphology of deglaciated areas can be studied in great detail, especially with increasing availability of high resolution DTM data (e.g. Bradwell 2013;Hubbard et al, 2000;Johansson 1999;Lidmar-Bergström and Näslund 2002;Olvmo et al 1999). Geomorphological analysis of deglaciated gneiss terrains at different scales can potentially be used as analogues for the subglacial topography of gneiss-dominated beds under present-day ice sheets.…”
Section: Fig 1 Laurentide and Greenland Ice Sheets At The Late Glacmentioning
confidence: 99%
See 1 more Smart Citation
“…Kleman and Stroeven, 1997;Stroeven et al, 2006). Such results lend support to the notion that some glacially scoured landscapes may have been directly inherited from the pre-glacial pattern of deep weathering (Hall and Sugden, 1987;Olvmo et al, 1999;Olvmo and Johansson, 2002). In fact, the formation of large glacial troughs towards a maximum steady-state shape (Sugden, 1976(Sugden, , 1978Braun, 1989) may have been predominantly established through valley widening, as inferred from (i) restricted glacial erosion in the scoured landscape of Riksgränsen (Stroeven et al, 2002a; this study), as well as for some other scoured landscapes in northern Sweden (cf.…”
Section: Erosional Pattern Of the Riksgränsen Areasupporting
confidence: 71%
“…Hardness and joint density are therefore expected to provide strong controls on the mode of erosion (i.e., abrasion vs. plucking). Some studies have also shown that the final products of glacial erosion of bedrock surfaces vary with the degree of preglacial weathering (Lindström, 1988;Olvmo et al, 1999;Johansson et al, 2001a, b;2 Krabbendam & Glasser: Glacial erosion: Abrasion vs Plucking. MS for Geomorphology Olvmo and Johansson, 2002); in effect this means that the bedrock properties in the top few metres can be different than the bulk bedrock below.…”
Section: Introductionmentioning
confidence: 99%